The value of religious tolerance and controversy in the film “Tanda Tanya (?)”: Peirce’s semiotics - Kunti Zahrotun Alfi; Anik Mariyani (Priviet Social Sciences Journal, 2026)
The development of the times has brought changes in people's mindsets and perspectives, including the interpretation of religious tolerance and controversy in pluralistic Indonesia. This change is supported by various media as part of technological development. Movies are one such medium. Film, as a visual communication medium, functions not only as entertainment but also as a means of conveying social and cultural values through a signal/sign system. This study aims to describe the sign system that represents the value of religious tolerance and controversy in the film ‘Tanda Tanya (?)’ by Hanung Bramantyo. This study used a qualitative approach with data collection techniques in the form of documentation, namely, repeated monitoring to understand the context thoroughly. Data in the form of film scenes were analyzed using Charles Sanders Peirce's semiotic theory, which includes icons, indexes, and symbols. The results showed that there were 11 scenes that represented the value of religious tolerance and controversy. Based on this data, each data point represents a system of three sign systems that specifically find 17 symbols, 16 indexes, and 13 icons. The dominant data found was a system of symbolic signs in the form of certain words, actions, colors, and goods that represent the value of religious tolerance and its controversy. This means that symbols with conventional properties in society are an effective means of instilling these values in the flow of the film.